2013
DOI: 10.1111/afe.12027
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of two different development patterns in Lobesia botrana (Lepidoptera: Tortricidae) larvae during the second generation

Abstract: 1 In north-eastern Italy, the second-generation larvae of Lobesia botrana (Den. & Schiff.) (Lepidoptera: Tortricidae) can develop with two different time patterns. In particular, in 'warmer' areas, the developmental time is shorter than in 'cooler' areas and it is associated with an earlier and more economically important third generation. 2 Because the differences in temperature are not sufficient to explain the two patterns, research was carried out aiming to investigate whether the differences in larval dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…At this stage, it is difficult to make sound predictions on the general significance of developmental traps across species and climate zones. Under variable conditions the co‐occurrence of different developmental patterns within a generation may provide resilience at the population level (Pavan et al ). We argue that the profile of species particularly susceptible to developmental trapping are multivoltine species that show strong thermal plasticity of development and use photoperiod as an important cue for life‐cycle regulation.…”
Section: Climate Change and Phenologymentioning
confidence: 99%
“…At this stage, it is difficult to make sound predictions on the general significance of developmental traps across species and climate zones. Under variable conditions the co‐occurrence of different developmental patterns within a generation may provide resilience at the population level (Pavan et al ). We argue that the profile of species particularly susceptible to developmental trapping are multivoltine species that show strong thermal plasticity of development and use photoperiod as an important cue for life‐cycle regulation.…”
Section: Climate Change and Phenologymentioning
confidence: 99%
“…Altermatt () reported that climate warming increased voltinism based on observation data of Central European Lepidoptera. Furthermore, studies reporting on the effects of local and annual temperature differences on the number of generations per year support the expected effect of climate warming on insect life cycles, for example, in Coleoptera (Hurpin, ; Pineau et al ., ), Hemiptera (Hulle et al ., ; Musolin et al ., ; Takeda et al ., ), and Lepidoptera (Crozier, ; Pavan et al ., ). Under gradual warming conditions, changes in voltinism are expected (Kiritani, ; Musolin, ) and deserve further research.…”
Section: Introductionmentioning
confidence: 97%
“…The European grapevine moth Lobesia botrana (Denis & Schiffermüller) (Lepidoptera: Tortricidae) is considered as a major pest in many European and Mediterranean vineyards and was also found recently in the Americas (Ioriatti et al ., ). It is a polyvoltine species with two to four generations per year, depending on latitude, microclimatic conditions and year (Martín‐Vertedor et al ., ; Caffarra et al ., ; Pavan et al ., ; Gilioli et al ., ). From the second generation, larvae are carpophagous and can cause yield losses and favour the spread of grapevine bunch rots, mostly Botrytis cinerea Pers.…”
Section: Introductionmentioning
confidence: 99%